1984
DOI: 10.1111/j.1748-1716.1984.tb07381.x
|View full text |Cite
|
Sign up to set email alerts
|

Breathing pattern and lung volumes during exercise

Abstract: The interrelationships of ventilation (V), tidal volume (VT), inspiratory (T1), expiratory (TE) and total breath (Ttot) durations, mean inspiratory (VT/TI) and expiratory (VT/TE) flows, and lung volumes were studied in normal subjects at rest and during exercise on a cycle ergometer. The ergometric load was increased by 10 W every minute, from zero W to 200 W. The TI/Ttot ratio increased with V in the range 15 to 60 1 X min-1, indicating that with increasing V the rate of increase of VT/TI decreased whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 18 publications
4
19
0
Order By: Relevance
“…In the study of Bechbache et al (1979), a similar result has been observed for subjects who entrained their f to pedal rate. No such decreases in TI and TE have been found in the study of Lind & Hesser (1984). These aspects led us to suspect that our subjects might have displayed an entrainment off to pedal rate.…”
Section: Discussionmentioning
confidence: 67%
“…In the study of Bechbache et al (1979), a similar result has been observed for subjects who entrained their f to pedal rate. No such decreases in TI and TE have been found in the study of Lind & Hesser (1984). These aspects led us to suspect that our subjects might have displayed an entrainment off to pedal rate.…”
Section: Discussionmentioning
confidence: 67%
“…Objective exercise effort was assessed by the peak respiratory exchange ratio (VCO 2 /VO 2 ). Ventilatory efficiency was assessed by the slope of V E to VCO 2 , and ventilatory drive was assessed by the ratio of V T to T I (8). All analyses of ventilation and gas exchange data were conducted offline in a blinded fashion.…”
Section: Methodsmentioning
confidence: 99%
“…1; Grimby, Saltin & Wilhelmsen, 1971;Lind & Hesser, 1984;Jones et al 1985;Leblanc, Summers, Inman, Jones, Campbell & Killian, 1988 Work rate 3 (177 W). Between 6 and 37+ 6-6 min, Vo increased from 2-35 to 2-84 1 min-'; VC02 increased from 2-28 to 2-61 1 min-'; RER fell from 0 97 to 0-92.…”
Section: Incremental Exercisementioning
confidence: 99%